Coexistent Isolated Tumor Cell Clusters of Infiltrating Lobular Carcinoma and Benign Glandular Inclusions of Müllerian (Endosalpingiosis) Type in an Axillary Sentinel Node: Case Report and Review of the Literature. Issue 2 (February 2016) - Groth, John V.; Prabhu, Sanjiv; Wiley, Elizabeth
Abstract : The presence of benign epithelial inclusions in axillary lymph nodes coexistant with breast disease is a rare event; however, their presence makes the assessment of nodal disease diagnostically challenging. Broadly, these inclusions can be classified as glandular (müllerian type or nonmüllerian type), mixed glandular-squamous, and squamous. Among these the presence of benign müllerian-type glandular inclusions with concurrent breast parenchymal disease is an exceedingly rare event, with 10 previous cases reported in the literature, 2 coexisting with infiltrating ductal-type mammary carcinoma in axillary lymph nodes. Here, we report the first case of coexistent invasive lobular carcinoma and endosalpingiosis in an axillary lymph node.